The Problem of Evil in the Eschatology of Maximus the Confessor - Makohon, Anatolii (Studia Warmińskie, 2019)
The article investigates the teaching about evil in the philosophy of Christian theologian Maximus the Confessor. The problem is being solved in the sphere of eschatological views of the thinker, which are yet to be thoroughly covered in science. Using the historic-philosophical methodology, the author looks into the most influential concepts of evil in philosophies of Maximus’s both non-Christian and Christian predecessors. Having borrowed their concept of voidness of being and weakening of natural powers in relation to evil, Maximus also developed his own understanding. It reveals in his eschatological teaching in which the goal of human’s being is the state of deification and ever-moving repose. In this state, gnomic will responsible for committing evil is deactivated. By overcoming Hellenic cyclic metaphysics and placing perfection at the end, and not the beginning, Maximus denies the concept of eternal return, strongly pronounced metaphysically in the Neoplatonic triad of “remaining – procession – reversion”. The teaching of independent Incarnation of Logos overcomes the Hellenic view of necessity of evil and eternity of the world, too. Maximus’s unique understanding of restoration and principle exhaustibility and finiteness of evil leaves certain evil beings, however, in the state of unbelonging to blessings. Approaching to solving the source of evil through investigation of the eschatology of Maximus the Confessor, the author gives a new viewpoint on the Reverend Father’s teaching.